Test-Day and Other Milk Recording Options for Prediction of Lactation Milk Yield in Gir (Bos indicus) Cows - Chaudhari, Pravin N.; Kapadiya, Pratik S.; Gadariya, Mahesh R.; Gamit, Pranav M.; Savaliya, Bhagavanji D. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
In the field condition, various milk recording options or test-day recording can be a useful tool to approximate/predict the production  potential of field bovines. Therefore, a study was carried out to approximate/predict standard lactation milk yield in Gir (Bos indicus) cows from different milk recording options and test-day milk yield. A total of 2,24,748 daily morning and evening milk production  performance records in 300 lactations of 50 Gir cows lactating at the Cattle Breeding Farm, JAU, Junagadh (Gujarat) over a period of  31 years (1986-2016) were used for the study. Test day records, 125, 155, and 185th at mid-and late lactations, i.e., 4, 5, and 6th month,  alone or combining consecutive two or three variables and even test day records 155th to 275th, i.e., from 5th to 9th month along with  daily peak yield were found important in determining the SLMY. Sum-up of morning and evening milk yield at weekly intervals till the  cow dries could be used to estimate lactation milk yield by the equation 0.59+6.97×Sum or sum-up of morning and evening milk yield  records at the fortnightly interval by the equation 21.23+14.73×Sum, with a precision of 99%.
Keywords: Gir (Bos indicus) cow; Milk recording options; Peak yield; Prediction of lactation yield; Test-day milk yield